Formulación de los Subprocesos Administrativos dentro del Proceso Agregador de Valor “Gestión de Posgrado” para la Gestión por Resultados en la Universidad Nacional De Loja, año 2022 - Chamba Andrade, Jefferson Paul (2023)
As one of the main approaches of the New Public Management at the National University of Loja, is to elaborate the manual of the administrative subprocesses of the Value Added process "Postgraduate Management". The Postgraduate Directorate is in charge of this process, which started working on April 01, 2022, which makes it a recently created directorate. As a result, the sub-process manuals did not exist. Furthermore, the UNL's organic regulation of organizational management does not identify its subprocesses. In order to acquire the results and analyze them, a qualitative approach with analytical and synthetic methods was required. In a first scenario, the situational diagnosis of the Postgraduate Department, consequently the existing problems. Also, to obtain information, gathering instruments (observation form and semi-structured interview) were used to obtain data from the management and then the collection of information to identify all the indispensable aspects in the development of the administrative sub-processes, thus establishing the activities, persons in charge, the times of each activity or task, the main inconveniences and the possible improvements, as the main proposal to achieve the change from a functional vision to a vision by processes. Public administration graduates' career profiles are directly impacted by this research. As part of the development of the Postgraduate Department's administrative subprocesses manual, knowledge acquired throughout academic training is required.